Penegakkan Hukum Oleh Kepolisian Terhadap Preman Yang Melakukan Pemalakan Di Angkutan Umum(Studi Kasus Polresta Padang) - Kevin Kurniawan; Sry Wahyuni; Elwidarifa Marwenny (CV. ITTC INDONESIA, 2024)
This thesis is entitled Enforcement of The Law By The Police Against Thugs Who Commit Public Transport Avoidance. Which in writing uses normative research methods, using the and case studies, research that examines the factual implementation or implementation of positive legal provisions in each specific legal event. The formulation of the problem in this research is: (1) What are the law enforcement efforts carried out by the police in dealing with thuggery in Padang City. (2) What are the obstacles faced by the Police in dealing with thuggery in Padang City? From the legal research that has been carried out using the research mentioned above, it can be concluded that, in the first problem formulation, law enforcement efforts have been carried out in a repressive and preventive manner, but in practice law enforcement administrators in the field often experience conflict between legal certainty and justice. This is because the conception of justice is an abstract formulation, while legal certainty is a procedure that has been determined normatively. Meanwhile, the second problem formulation discusses the obstacles faced by the police in dealing with thuggery in Padang City, such as internal obstacles and external obstacles.